A Note on the Decomposition of Aerodynamic Forces Induced by a Wind Turbine Flaps. (6th August 2020) - Niu, Y. Y.; Shih, P. J.; Kong, S. C.
Abstract : In this study, the aerodynamic characteristics of a vertical-axis wind turbine blade coupled with a high-lift device, such as the Gurney flap at the trailing edge, are investigated. For numerical analysis, the force element theory is used to understand how the Gurney flap influences the force evolution of the lift-type vertical-axis wind turbine. This study shows that the lift and drag can be respectively approximated into four elements, which are induced by volume vorticity, rotational velocity, angular acceleration and surface friction of the flow around the blades. Based on the perspective of the force element theory, the present simulation provides a clear picture of how the Gurney flap influences the formation of the aerodynamic force elements during a rotational cycle for a vertical-axis wind turbine. Simulation results show that the contributions mainly result from the surface vorticities, the rotational acceleration of the airfoil, and the acceleration of the surface.